2022-RA-576-ESGO Expression VIII – first study of individual perception and level of information of patients with low grade ovarian cancer and borderline tumor of the ovary in 321 patients. (20th October 2022) - Beckmann, Laura Naomi; Alavi, Sara; Keller, Maren; Liebrich, Clemens; Kubiak, Karol; Wimberger, Pauline; Czolk, Vera; Ligl-Löhner, Anette; Enzinger, Hans-Martin; Burdack, Aline; Fischer, Dorothea; Terhaag, Jürgen; et al.
Abstract : Introduction/Background: Low-grade serous carcinomas (LGSC) are associated with better prognoses compared to their high-grade serous (HGSC) counterparts. Nevertheless, we are confronted with a challenging treatment, since the median age upon diagnosis is younger, standard platinum-based chemotherapy is less effective and, most importantly, it has still not been as well studied as HGSC. The purpose of this ongoing study was to examine patients' perception and assessment regarding their disease and therapy as well as the level of information among women with LGSC and borderline ovarian tumors (BOT). Methodology: A questionnaire was developed based on the experiences of previous EXPRESSION-trials and provided to patients with LGSC and BOT. The hardcopy-version was converted into an online database and statistically analyzed via SPSS-Software. Results: From March 2019, 321 patients with LGSC and BOT from eighteen German clinics and gynecological practices participated in the survey, 90 (28%) with LGSC and 231 (72%) with BOT. While nearly all patients (97.8% LGSC; 94.3% BOT) had primary surgery, 58% of LGSC patients received adjuvant chemotherapy. Patients indicated the attending physician as the main source of information (81% LGSC; 85% BOT). The majority were pleased with the explanation about their illness and therapy. Significantly more BOT-patients were not aware of their tumor stage during initial diagnosis (31.4% LGSC vs 64.5% BOT, p= <0.0001). 47.8% of LGSC-patients did not know the difference between LGSC and HGSC and 73.9% were not offered a hormone replacement therapy. BOT-patients estimate the aggressiveness (31.2% BOT vs. 52.2% LGSC) and the risk of recurrence (28.2% BOT vs. 44% LGSC) of their disease lower than LGSC-patients. Conclusion: This study underlines the high need for more detailed explanation in this specific patient group with a greater focus on the underlying tumor biology and the corresponding course of disease and prognosis.